A battery and an electric device
Patent Information
- Application Number
- CN202510424971.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]针对现有锂金属电池在高电压充放电过程中电池性能下降的问题,本发明提供了一种电池及用电装置
[0021] In this invention, on the one hand, the ion-solvent coordination environment is reconstructed through the interaction between additives and solvents, reducing the energy consumption of the carrier desolvation process. Simultaneously, the microscopic transport path of the electrolyte is optimized, achieving rapid desolvation of the electrode-electrolyte interface. The electrolyte viscosity in this application is 4–15 mPa·s, which is relatively low, and the ionic conductivity reaches 2.8–5.1 mS/cm. This high-conductivity electrolyte design improves lithium-ion transport at the positive and negative electrode interfaces, ensuring the battery maintains excellent rate performance even at high voltages. On the other hand, by setting an SEI layer and/or a lithium alloy layer on the surface of the negative electrode active material, rapid ion conduction is achieved, and the growth of lithium dendrites at high rates is slowed down, further improving the battery's rate performance.
Smart Images

Figure CN122931031A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a battery and an electrical device. Background Technology
[0002] With the rapid development of electric vehicles and mobile electronic devices, the demand for energy density, safety, and cycle performance of rechargeable batteries is increasing. Energy density and cycle performance are crucial parameters for evaluating rechargeable battery performance. Lithium metal has the lowest relative atomic mass (6.94) and the lowest standard electrode potential (-3.045V) among all metallic elements, with a theoretical specific capacity of 3860mAh / g. Therefore, using lithium metal as the negative electrode, combined with high-energy-density positive electrode materials, can significantly improve the battery's energy density (>400Wh / kg) and operating voltage (>4.5V). Lithium metal batteries typically use lithium-coated copper strips as the negative electrode. However, lithium metal is highly reactive; during high-rate charge and discharge, the electric field changes drastically, leading to uneven lithium-ion deposition and dendrite formation after nucleation. This results in a decrease in the coulombic efficiency of lithium metal, affecting charge and discharge performance at high rates.
[0003] Therefore, there is an urgent need to develop a lithium metal battery that maintains excellent rate performance even at high voltage. Summary of the Invention
[0004] To address the problem of performance degradation in existing lithium metal batteries during high-voltage charging and discharging, this invention provides a battery and an electrical device.
[0005] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a battery comprising an electrolyte, a negative electrode, and a positive electrode. The electrolyte comprises a lithium salt, an additive, and a solvent. The additive comprises at least two of the following: fluoroethylene carbonate, 1,3-propane sulpholol, vinylene carbonate, vinyl sulfate, a lithium supplement, tris(trimethylsilane) phosphate, tris(trimethylsilyl)borate, dimethyldimethoxysilane, and an ionic liquid. The solvent comprises at least one of a silane solvent and an ether solvent. The negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer, and a functional layer. The negative electrode active material is disposed on at least one side of the negative electrode current collector, and the functional layer is disposed on the side of the negative electrode active material layer opposite to the current collector. The functional layer is an SEI layer and / or a lithium alloy layer. The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes a positive active material.
[0006] Optionally, the silane solvent includes one or more of trimethylmethoxysilane, methyltrimethoxysilane, tetramethyl orthosilicate, (3,3,3-trifluoropropyl)-dimethylmethoxysilane, and (3,3,3-trifluoropropyl)-trimethoxysilane; And / or, the ether solvent includes one or more of the following: fluoroether compounds, 2-dimethoxyethane, ethylene glycol dimethyl ether, dimethoxydimethyl ether, diethylene glycol dimethyl ether, 1,3-dioxolane, triethylene glycol monoethyl ether, tetrahydrofuran, and 2-methyl-tetrahydrofuran; The fluoroether compounds include one or more of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, methoxynonfluorobutane, ethoxynonfluorobutane, and 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane.
[0007] Optionally, the ionic liquid comprises one or more of the following: 1-methyl-propylpyrrolidone bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpiperidine bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidine bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidine bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidone bis(fluorosulfonyl)imide, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide. And / or, the lithium supplement includes one or more of lithium nitrate, lithium borate, lithium difluorooxalate borate, lithium difluoro(bis(oxalate) phosphate), and lithium difluorophosphate.
[0008] Optionally, the mass of the additive is 0.01% to 10% of the mass of the solvent, and the concentration of the lithium salt is 1 to 4 mol / L.
[0009] Optionally, the SEI layer includes one or more of lithium fluoride, lithium oxide, lithium sulfide, lithium nitride, and lithium phosphide; And / or, the lithium alloy layer comprises an alloy formed of metallic lithium with one or more of gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth.
[0010] Optionally, the thickness of the functional layer is 0.2~20μm.
[0011] Optionally, the particle size distribution of the positive electrode active material satisfies K90 > 0.6.
[0012] Optionally, the positive current collector and the negative current collector are each independently selected from metal current collectors and / or composite current collectors; The composite current collector includes a base film, a substrate layer, and a conductive layer. The substrate layer is disposed between the base film and the conductive layer and is located on at least one side of the base film. The substrate layer includes at least one of nickel and titanium.
[0013] Optionally, the negative electrode current collector further includes a coating layer disposed on at least one surface of the metal current collector and located between the negative electrode active material layer and the metal current collector; and / or, the coating layer is disposed between the underlayer and the conductive layer; The coating includes one or more of the following elements: nickel, zinc, tin, silver, magnesium, iron, aluminum, and boron.
[0014] Optionally, when the positive current collector and the negative current collector are selected from composite current collectors, both the positive electrode and the negative electrode are provided with adapter tabs and external tabs. The adapter tabs are welded to the conductive layer. The conductive layer, on the side facing away from the base film, is provided with an adapter tab connection area, a blank area and an active material area for coating active materials in sequence along its length direction. The adapter tab includes a first connection area and a second connection area. The first connection area is connected to the adapter tab connection area and partially connected to the blank area. The end of the second connection area away from the blank area is soldered to the external tab. The length of the first connection area is less than or equal to the length of the blank area, the length of the second connection area is less than or equal to the length of the first connection area, and the width of the first connection area is greater than the width of the second connection area.
[0015] Optionally, the first connection area is welded to the adapter tab connection area, the weld marks are spaced apart, the shape of the weld marks is rhomboid, square or circular, and the gap between two adjacent weld marks is 0.1~1mm.
[0016] Optionally, when the solder mark is rhomboid, the ratio of the diagonal lengths of the solder mark is 1:1 to 5:1; And / or, when the solder mark is square, the diagonal length of the solder mark is 1.44~7mm; And / or, when the solder mark is circular, the diameter of the solder mark is 1~5mm.
[0017] Optionally, the cross-sectional area of the external electrode tab is 0.05-40 mm. 2 ; And / or, the thickness of the outer tab of the positive electrode sheet is 100~300μm, the width is 5~65mm, and the length is 20~60mm; The thickness of the external tab of the negative electrode sheet is 100~400μm, the width is 5~65mm, and the length is 20~60mm.
[0018] Optionally, the battery further includes a separator, which is a polymer porous base membrane or a coated separator, wherein the coated separator includes a polymer porous base membrane and a functional coating disposed on at least one side of the polymer porous base membrane; The polymer porous base membrane includes at least one of polyethylene and polypropylene; the functional coating includes one or more of ion conduction enhancers, polymer binders, thickeners, and wetting agents.
[0019] Optionally, the ion conduction enhancer includes one or more of the following: oxide solid electrolyte, halide solid electrolyte, sulfide solid electrolyte, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, barium sulfate, polyvinylidene fluoride and its copolymers, aramid, polymethyl methacrylate and its modifiers.
[0020] Secondly, the present invention also provides an electrical device including the battery described above.
[0021] In this invention, on the one hand, the ion-solvent coordination environment is reconstructed through the interaction between additives and solvents, reducing the energy consumption of the carrier desolvation process. Simultaneously, the microscopic transport path of the electrolyte is optimized, achieving rapid desolvation of the electrode-electrolyte interface. The electrolyte viscosity in this application is 4–15 mPa·s, which is relatively low, and the ionic conductivity reaches 2.8–5.1 mS / cm. This high-conductivity electrolyte design improves lithium-ion transport at the positive and negative electrode interfaces, ensuring the battery maintains excellent rate performance even at high voltages. On the other hand, by setting an SEI layer and / or a lithium alloy layer on the surface of the negative electrode active material, rapid ion conduction is achieved, and the growth of lithium dendrites at high rates is slowed down, further improving the battery's rate performance. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the structure of a positive electrode (negative electrode) of a battery according to an embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a positive electrode (negative electrode) of a battery provided in another embodiment of the present invention.
[0023] Labels in the attached diagram: 1. Blank area; 2. Active material area; 3. First connection area; 4. Second connection area. Detailed Implementation
[0024] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0025] An embodiment of the present invention provides a battery comprising an electrolyte, a negative electrode, and a positive electrode. The electrolyte comprises a lithium salt, additives, and a solvent. The additives include at least two of the following: fluoroethylene carbonate (FEC), 1,3-propane sulpholol, vinylene carbonate (VC), vinyl sulfate, lithium supplement, tris(trimethylsilane) phosphate (TMSP), tris(trimethylsilyl)borate (TMSB), dimethyldimethoxysilane (DMMS), and ionic liquids. The solvent comprises at least one of the following: silane solvents and ether solvents.
[0026] The negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer, and a functional layer. The negative electrode active material is disposed on at least one side of the negative electrode current collector, and the functional layer is disposed on the side of the negative electrode active material layer opposite to the current collector. The functional layer is an SEI (solid electrolyte interphase) layer and / or a lithium alloy layer. The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes a positive active material.
[0027] In this invention, on the one hand, the ion-solvent coordination environment is reconstructed through the interaction between additives and solvents, reducing the energy consumption of the carrier desolvation process. Simultaneously, the microscopic transport path of the electrolyte is optimized, achieving rapid desolvation of the electrode-electrolyte interface. The electrolyte viscosity in this application is 4–15 mPa·s, which is relatively low, and the ionic conductivity reaches 2.8–5.1 mS / cm. This high-conductivity electrolyte design improves lithium-ion transport at the positive and negative electrode interfaces, ensuring the battery maintains excellent rate performance even at high voltages. On the other hand, by setting an SEI layer and / or a lithium alloy layer on the surface of the negative electrode active material, rapid ion conduction is achieved, and the growth of lithium dendrites at high rates is slowed down, further improving the battery's rate performance. Furthermore, the particle size distribution of the positive electrode active material in the positive electrode sheet satisfies K90 > 0.6, resulting in pores of various sizes within the positive electrode active material layer. The larger pores formed between the large particles of positive electrode active material facilitate electrolyte penetration and ion transport within the electrode, providing a rapid migration channel for lithium ions. Conversely, the tiny pores surrounding the small particles of positive electrode active material increase the contact area between the active material and the electrolyte, thus enhancing reactivity. The particle size distribution of the positive electrode active material, along with the negative electrode sheet and the electrolyte, works together to further improve the battery's charge / discharge efficiency and rate performance.
[0028] In one embodiment, the silane solvent includes one or more of trimethylmethoxysilane (TMOS), methyltrimethoxysilane, (TOS), (3,3,3-trifluoropropyl)-dimethylmethoxysilane (TFMDS), and (3,3,3-trifluoropropyl)-trimethoxysilane (TFTMS). The conjugation between the empty Si 3d orbitals of the siloxane molecules and the lone pair electrons of the O atoms in the silane solvent reduces the solvation ability of lithium ions, achieving rapid desolvation at the interface, thereby enabling rapid lithium ion conduction and improving the rate performance of the battery cell system.
[0029] The ether solvents include one or more of the following: fluoroether compounds, 2-dimethoxyethane (DME), ethylene glycol dimethyl ether (EDG), dimethoxydimethyl ether (DMM), diethylene glycol dimethyl ether (DG), 1,3-dioxocyclopentane (DOL), triethylene glycol monoethyl ether (Trig), tetrahydrofuran (THF), and 2-methyl-tetrahydrofuran (2-Me-THF).
[0030] The fluoroether compounds include one or more of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), methoxynonfluorobutane (MOFB), ethoxynonfluorobutane (EOFB), and 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane (BTFEE).
[0031] The viscosity of the electrolyte can be adjusted by using silane solvents, fluoroether compounds, or other ether solvents mentioned above.
[0032] Specifically, when the solvent is a silane solvent and an ether solvent, the molar ratio is 1:(0.5~2).
[0033] In some embodiments, the ionic liquid comprises one or more of 1-methyl-propylpyrrolidone bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpiperidine bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidine bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidine bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidone bis(fluorosulfonyl)imide (Pyr13FSI), and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMMIFSI).
[0034] The lithium supplementer includes one or more of lithium nitrate, lithium borate, lithium difluorooxalate borate, lithium difluoro(bis(oxalate) phosphate), and lithium difluorophosphate (LiDFP). The ionic conductivity of the electrolyte is further controlled by adding ionic liquids and lithium supplementers to the electrolyte.
[0035] In some embodiments, the mass of the additive is 0.01% to 10% of the mass of the solvent, and the concentration of the lithium salt is 1 to 4 mol / L. By limiting the mass of the additive and the concentration of the lithium salt, the additive and solvent in the electrolyte can interact to reconstruct the ion-solvent coordination environment, while the ionic conductivity of the electrolyte can be controlled to reach 2.8 to 5.1 mS / cm.
[0036] In a preferred embodiment, the mass of the additive is 0.5% to 5% of the mass of the solvent, and the concentration of the lithium salt is 1.5 to 3 mol / L.
[0037] Specifically, the mass of the additive is 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, 2%, 2.4%, 2.8%, 3.2%, 3.6%, 4%, 4.4%, 4.8%, or 5% of the mass of the solvent, but is not limited to the above limitations, as long as the mass of the additive is 0.5% to 5% of the mass of the solvent. The concentration of the lithium salt includes, but is not limited to, 1.5M, 1.7M, 1.9M, 2.1M, 2.3M, 2.5M, 2.7M, or 3M.
[0038] In some embodiments, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bisfluorosulfonylimide (LiFSI), lithium trifluoromethanesulfonyl-perfluorobutylsulfonylimide (LiTNFSI), lithium fluorosulfonyl-perfluorobutylsulfonylimide (LiFNFSI), lithium bis(oxalatoborate)borate (LiBOB), and lithium difluorophosphate (LiPO2F2).
[0039] In some embodiments, the SEI layer includes one or more of lithium fluoride, lithium oxide, lithium sulfide, lithium nitride, and lithium phosphide.
[0040] The lithium alloy layer comprises an alloy of metallic lithium with one or more of the following: gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth. By preparing the aforementioned SEI layer and lithium alloy layer, direct contact between metallic lithium and the electrolyte / electrolyte can be effectively avoided, promoting uniform deposition of lithium ions and diffusion within the lithium metal anode. This effectively improves issues such as SEI film thickening and continuous lithium dendrite growth, thereby enhancing the safety performance of the battery cell.
[0041] In some embodiments, the thickness of the functional layer is 0.2~20μm. By adjusting the thickness of the SEI layer and the lithium alloy layer, the energy density of the battery can be increased while avoiding the growth of lithium dendrites without affecting the battery's charging and discharging.
[0042] Specifically, the thickness of the functional layer includes, but is not limited to, 0.2μm, 0.5μm, 1μm, 3μm, 5μm, 7μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 15μm, 17μm, 19μm or 20μm.
[0043] In some embodiments, the positive current collector and the negative current collector are each independently selected from metal current collectors and / or composite current collectors.
[0044] The composite current collector includes a base film, a substrate layer, and a conductive layer. The substrate layer is disposed between the base film and the conductive layer, and is located on at least one side of the base film. The substrate layer includes at least one of nickel and titanium. By providing the substrate layer, the adhesion between the conductive film layer and the base film is increased.
[0045] Specifically, when the electrode is a positive electrode, the metal foil is aluminum foil, and the conductive layer is metallic aluminum. When the electrode is a negative electrode, the metal foil is copper foil, and the conductive layer is one or more of copper, nickel, copper-nickel, and copper-zinc alloys.
[0046] The base film includes one or more of polyethylene, polyethylene terephthalate, polyimide, polypropylene, polyamide, polyphenylene sulfide, and polyethylene naphthalate.
[0047] In some embodiments, the negative electrode current collector further includes a plating layer disposed on at least one surface of the metal current collector and located between the negative electrode active material layer and the metal current collector. And / or, the plating layer is disposed between the underlayer and the conductive layer.
[0048] The coating comprises one or more elements selected from nickel, zinc, tin, silver, magnesium, iron, aluminum, and boron. By applying the coating, the conductivity of the current collector is enhanced, lithium dendrite growth is suppressed, and the current collector is prevented from being corroded by the electrolyte. This coating can be prepared using dry methods (such as physical vapor deposition, PVD) and / or wet methods (chemical vapor deposition, CVD, or electroplating).
[0049] Furthermore, in some embodiments, the thickness of the aluminum foil in the positive electrode sheet is 2~15μm, the thickness of the base film is 1~8μm, the thickness of the conductive layer is 0.2~10μm, and the thickness of the underlayer is 10~1000nm. By controlling the thickness of the aluminum foil and the positive current collector in the positive electrode sheet, the quality of the positive electrode sheet can be further controlled, so as to improve the mass energy density of the battery.
[0050] In the negative electrode sheet, the thickness of the copper foil is 2~12μm, the thickness of the base film is 1~6μm, the thickness of the conductive layer is 0.1~10μm, the thickness of the plating layer is 0.01~1μm, and the thickness of the underlayer is 10~500nm. By controlling the thickness of the copper foil and the negative electrode current collector in the negative electrode sheet, the quality of the negative electrode sheet can be further controlled, thereby improving the mass energy density of the battery.
[0051] In some embodiments, the positive electrode active material layer comprises 70% to 99.9% positive electrode active material, 0.05% to 15% electronic conductive agent, and 0.05% to 15% additives. By controlling the content of each component in the positive electrode active material layer, the areal density, compaction density, porosity, thickness, and areal specific capacity of the positive electrode sheet can be adjusted, thereby improving the mass energy density and volumetric energy density of the battery.
[0052] Positive electrode active materials include LiNi x Mn y Co z O2 (0.3≤x≤0.99, x+y+z=1), LiNi x Al y Co z O2 (0.3≤x≤0.99, x+y+z=1), lithium manganese iron phosphate (LiFe) x Mn y The cathode modification materials include: lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), lithium-rich manganese-based (xLi2MnO3·(1-x)LiMO2, M=Ni, Co, Mn or one or more), lithium nickel manganese oxide (LMNO), lithium vanadium phosphate (Li3V2(PO4)3), lithium vanadium oxide phosphate (LiVOPO4), and one or more of the above cathode modification materials.
[0053] The areal density of the positive electrode sheet is 10~30 mg / cm³. 2 The compaction density of the positive electrode sheet is 2.5~3.8 mg / cm³. 3 The thickness of the positive electrode sheet is 50~300μm, the porosity of the positive electrode sheet is 1~40%, and the areal specific capacity is 2~10mAh / cm³. 2The sheet resistance of the positive electrode is 1-300 mΩ / sq. Positive electrode sheets that meet the above conditions can achieve high areal density and high compaction density, thereby improving the mass energy density and volumetric energy density of the battery.
[0054] In some embodiments, the particle size distribution of the positive electrode active material satisfies K90 > 0.6. Specifically, K90 = (D90 - D10) / D50, where K90 is an index that measures the width of the particle size distribution of the material. The larger the K90 value, the wider the particle size distribution.
[0055] The particle size distribution of the positive electrode active material in the positive electrode sheet satisfies K90 > 0.6, resulting in pores of various sizes within the positive electrode active material layer. The larger pores formed between the larger positive electrode active material particles facilitate electrolyte penetration and ion transport within the electrode, providing a rapid migration channel for lithium ions. Conversely, the tiny pores surrounding the smaller positive electrode active material particles increase the contact area between the active material and the electrolyte, thus enhancing reactivity. The particle size distribution of the positive electrode active material, along with the negative electrode sheet and the electrolyte, works together to further improve the battery's charge / discharge efficiency and rate performance.
[0056] Furthermore, the cathode material particles have a D50 of 0.1~20μm, a D90 of 0.15~50μm, and a D10 of 0.05~18μm.
[0057] In this embodiment, the center position of the positive electrode sheet in the longitudinal direction is used as the dividing line, and the absolute value of the K90 difference between the particles on both sides is K, where K is greater than or equal to 0. In particular, when K is 0, the particle size and distribution of the positive electrode powder are obtained by extracting the positive electrode powder, and its K90 is greater than 0.6.
[0058] Further, in one embodiment, the electronically conductive agent includes one or more of graphite, hard carbon, soft carbon, carbon nanotubes, graphene, porous carbon, superconducting carbon black, acetylene black, furnace black, and vapor-grown carbon fiber (VGCF).
[0059] The additives include one or more of the following: polytetrafluoroethylene and its derivatives, polyvinylidene fluoride and its derivatives, silicone rubber, styrene-butadiene rubber, hydrogenated nitrile rubber, boronized polyethylene glycol, cellulose, cellulose esters, cellulose ethers, nitrocellulose, carboxyalkyl cellulose, cellulose salts, sodium carboxymethyl cellulose and cellulose salt derivatives, polyacrylic acid, polyamide, polyvinyl alcohol, polyethyleneimine, and polyimide.
[0060] The positive electrode sheet can be prepared by wet method, which involves mixing the positive active material, electronic conductive agent, additive and dispersant in a preset ratio to form a slurry, coating the obtained slurry on the current collector at a certain loading, and finally drying and rolling it at a temperature of 60℃~180℃ to form an electrode sheet.
[0061] Alternatively, a dry preparation method can be selected, in which the positive electrode active material, electronic conductive agent and additives are mixed in a preset ratio, shear force is applied to the mixed powder to make the additives fibrous, and a preform is obtained. The preform is then extruded or rolled into a self-supporting membrane with a thickness of 50~300μm.
[0062] Finally, the self-supporting film is loaded onto the current collector that rolls between two rollers, and rolled to form an electrode. The surface of this current collector can be coated with a carbon layer or conductive adhesive, with a thickness of 0~5μm.
[0063] In some embodiments, when the positive current collector and the negative current collector are selected from composite current collectors, both the positive electrode sheet and the negative electrode sheet are provided with adapter tabs and external tabs. The adapter tabs are welded to the conductive layer. The conductive layer, on the side facing away from the base film, is provided with an adapter tab connection area, a blank area 1 and an active material area 2 for coating active materials in sequence along its length direction.
[0064] The adapter tab includes a first connection area 3 and a second connection area 4. The first connection area 3 is connected to the adapter tab connection area and partially connected to the blank area 1. The end of the second connection area 4 away from the blank area 1 is soldered to the external tab.
[0065] The length of the first connection area 3 is less than or equal to the length of the blank area 1, the length of the second connection area 4 is less than or equal to the length of the first connection area 3, and the width of the first connection area 3 is greater than the width of the second connection area 4. By limiting the lengths of the first connection area 3 and the second connection area 4, the overcurrent capacity at the connection between the adapter tab and the current collector is effectively improved, mitigating the heating problem in the tab area under high-rate discharge caused by the thin conductive layer of the composite current collector, thus preventing thermal runaway of the battery. Through the synergistic effect of the adapter tab and the electrolyte and negative electrode, the high-rate discharge capability of the composite current collector electrode is further improved.
[0066] In one embodiment, when the positive and negative current collectors are selected from metal current collectors, alloying can be performed on the surfaces of the tab regions on the upper and lower surfaces of the electrode sheet, and on the surfaces of the tab-electrode connection regions (covering part or all of the overhang). This involves preparing films composed of alloying elements, with a thickness of 0.05-5 μm. Preparation methods include rolling, melt coating, and physical vapor deposition with a mask. For the negative current collector, the alloying elements can be one or more of elements such as zinc, tin, lead, phosphorus, silver, aluminum, nickel, and silicon. For the positive current collector, the alloying elements can be one or more of elements such as copper, zinc, manganese, silicon, magnesium, tin, lead, and zirconium. The introduction of this alloyed region can improve the connection strength between the electrode sheet region and the tab region, and also improve the current-carrying capacity of the tab region.
[0067] In some embodiments, the first connection area 3 is welded to the adapter tab connection area, and the weld marks are spaced apart. The weld mark shape is rhomboid, square, or circular, and the gap between two adjacent weld marks is 0.1~1mm. In this embodiment, the shape and structure of the weld mark can effectively increase the ratio of the perimeter to the area of the weld mark, thereby increasing the path length of current conduction with the same amount of welding material.
[0068] In some embodiments, when the solder mark is rhomboid, the ratio of the diagonal lengths of the solder mark is 1:1 to 5:1.
[0069] When the solder mark is square, the diagonal length of the solder mark is 1.44~7mm.
[0070] When the solder mark is circular, the diameter of the solder mark is 1~5mm.
[0071] The shape and structure of the solder mark in this embodiment enable the battery to discharge normally under 10C conditions.
[0072] In some embodiments, the cross-sectional area of the external electrode tab is 0.05-40 mm. 2 By limiting the cross-sectional area of the external tabs, the high-rate performance of the battery can be guaranteed.
[0073] In some embodiments, the thickness of the external tab of the positive electrode sheet is 100~300μm, the width is 5~65mm, and the length is 20~60mm.
[0074] The thickness of the external tab of the negative electrode sheet is 100~400μm, the width is 5~65mm, and the length is 20~60mm.
[0075] In some embodiments, the battery further includes a separator, which is a polymer porous base membrane or a coated separator, wherein the coated separator includes a polymer porous base membrane and a functional coating disposed on at least one side of the polymer porous base membrane.
[0076] The polymer porous base membrane includes at least one of polyethylene and polypropylene. The functional coating includes one or more of an ion conduction enhancer, a polymer binder, a thickener, and a wetting agent. By setting the functional coating, the ion conduction enhancer used has the advantages of large specific surface area and high conductivity, achieving high ion conductivity, thereby reducing the mass ratio of the separator and increasing the energy density of the battery. The included polymer binder improves the adhesion between the functional coating and the polymer porous base membrane, preventing the coating from falling off when the battery is subjected to external impacts. The included wetting agent is used to improve the wettability of the separator.
[0077] Specifically, the polymer porous base membrane has a porosity of 30%~80% and an air permeability of 20~200s / 100cc. The functional coating has at least one layer and can face either the positive or negative electrode.
[0078] In some embodiments, the ion conduction enhancer comprises one or more of the following: oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, barium sulfate, polyvinylidene fluoride and its copolymers, aramid, polymethyl methacrylate and its modifiers. Specifically, the ion conduction enhancer has an ionic conductivity ≥1×10⁻⁶. -5 mS / m.
[0079] Oxide solid electrolytes include, but are not limited to, LATP, LLZO, and LLZTO; halide solid electrolytes include, but are not limited to, Li3InCl6, Li2MnCl4, Li2ZnCl4, Li3YCl6, and Li6CoCl8; and sulfide solid electrolytes include, but are not limited to, Li3PS4 and Li7P3S. 11 , Li6PS5Cl, LSPSCl, Li4SnS4.
[0080] The polymer binder includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate and its copolymers, polyacrylic acid and its copolymers, lithium polyacrylate, polyacrylonitrile, styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyacrylamide, polyvinyl acetate and polyurethane.
[0081] The thickener includes one or more of carboxymethyl cellulose, sodium alginate, terpineol, polyacrylic acid, polyvinyl alcohol, xanthan gum, gum arabic, gelatin, and guar gum.
[0082] The wetting agent includes one or more of the following: polydimethylsiloxane, polyether-modified siloxane, polyoxyethylene ether, octylphenol polyoxyethylene ether, polyether siloxane, sodium alkylbenzene sulfonate, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, or sodium lauryl sulfate.
[0083] The separator prepared using the above materials can achieve high ionic conductivity and improve the rate performance of the battery.
[0084] Specifically, the coating diaphragm is prepared by one or more of the following methods: roller coating, spray coating, dot matrix coating, and intermittent coating, wherein the coating thickness is 0.5~5 μm, the drying temperature is 30~80 ℃, and the coating linear speed is 80~150 ms. -1 .
[0085] In one embodiment, the average particle size of the polymer binder is 0.1 to 10 μm. By using a polymer binder within this particle size range, uniformity during the application of the functional coating is ensured.
[0086] In one embodiment, the functional coating, based on 100% by mass, comprises the following components: 80%–99% ion conduction enhancer, 0–10% wetting agent, 0–10% polymer binder, and 0–10% thickener. By adjusting the content of each component of the diaphragm, the diaphragm exhibits good heat shrinkage resistance, puncture strength, and membrane rupture temperature.
[0087] In one embodiment, the battery capacity is 1Ah-200Ah; the battery nominal voltage is 3.0V-4.8V; and the battery can achieve a power output range of 0.2W-10000W.
[0088] Specifically, the discharge power temperature is -30-50℃, the charging power temperature is -20-50℃, the low-temperature test discharge temperature is -30-0℃, the room temperature test discharge temperature is 25℃, and the high-temperature test discharge temperature is 25-50℃; the cell state of charge (SOC) is 0-100%; the instantaneous discharge power time is 2s, 5s, 10s, and 30s; the continuous discharge power time is 60s and above; and the total energy of the battery is 3.0Wh-960Wh.
[0089] The battery operates at a voltage range of 2.0V-5.0V; its continuous charging capability is 0.1C-10C; its continuous discharging capability is 0.1C-6C; its peak discharge capability is 10C; and its 6C discharge capacity retention rate is >95% (vs 1C).
[0090] In one embodiment, the battery is encapsulated using an aluminum-plastic film, which is a multilayer composite film of nylon-aluminum layer-polypropylene (PP).
[0091] The total thickness of the aluminum-plastic film can range from 70 μm to 170 μm, and the areal density can range from 14.5 to 26.0 mg / cm². The thickness of the nylon layer can range from 15 μm to 25 μm, the thickness of the aluminum layer can range from 30 μm to 60 μm, and the thickness of the PP layer can range from 60 μm to 80 μm. By using the above-mentioned aluminum-plastic film, the battery can possess high tensile strength, high puncture resistance, and high elongation at break, ensuring that the battery maintains high safety performance even in extreme environments.
[0092] Specifically, the battery is manufactured as follows: 1. The positive electrode, the negative electrode, and the separator are stacked together to obtain a semi-finished stacked battery.
[0093] 2. Weld the positive and negative current collector tabs of the semi-finished stacked battery from step 1 to the external tabs, and then encapsulate them into the aluminum-plastic film to obtain the semi-finished battery.
[0094] 3. After adding the semi-finished battery from step 2 to the electrolyte, the battery is subjected to vacuum settling, formation, and degassing, and then the aluminum-plastic film is re-encapsulated to obtain the battery.
[0095] Specifically, the aluminum-plastic film is a multi-layer composite film composed of nylon, aluminum layer, and polypropylene (PP).
[0096] The thickness of the aluminum-plastic film can be 80μm-160μm.
[0097] The aluminum-plastic film is prepared by either a dry method or a hot method. The dry method involves bonding nylon, aluminum, and PP with an adhesive and then directly pressing them together. The hot method involves bonding nylon, aluminum, and polypropylene with microporous foamed polypropylene (MPP) and then slowly heating and pressing them together.
[0098] It should be noted that in the battery, the negative electrode has one more layer than the positive electrode; that is, the outermost layer of the semi-finished stacked battery is always a negative electrode sheet, and the outermost negative electrode sheet can be a single-sided active material, with the surface not facing the positive electrode sheet using an empty current collector. Alternatively, the outermost negative electrode sheet can also be a double-sided active material.
[0099] An embodiment of the present invention also provides an electrical device, including the aforementioned battery.
[0100] The present invention will be further illustrated by the following examples.
[0101] Example 1 This embodiment illustrates the battery disclosed in this invention and includes the following operational steps: Electrolyte: Solvent 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE) and trimethylmethoxysilane (TMOS) were mixed at a molar ratio of 1:0.9. Then, lithium difluorooxalate borate (LiDFOB) and lithium difluorophosphate (LiDFP) were added, with LiDFOB and LiDFP accounting for 0.5% of the solvent mass, respectively, to form a homogeneous and stable solution. Finally, LiFSI was added to form a lithium salt concentration of 2.86 M.
[0102] Battery manufacturing Preparation of positive electrode sheet Take the positive electrode active material Li according to a mass ratio of 93:4:3 x Ni n1 Mn n2 Co n3 Fe y O2+z The following conditions are met: 0.3≤x≤0.99, x+n1+n2+n3+y=1, n1 / n2=10. Conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed and then dispersed in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to obtain the positive electrode slurry. The obtained slurry is uniformly coated on both sides of the positive electrode current collector, and after drying, calendering, and further drying, the positive electrode sheet is obtained. The particle size distribution of the positive electrode active material is K90=0.98.
[0103] Preparation of negative electrode sheet The negative electrode uses a lithium metal negative electrode, and an SEI layer containing lithium fluoride and lithium nitride is formed on the surface of the lithium metal through physical vapor deposition, with a thickness of 1 μm.
[0104] Preparation of diaphragm Solid electrolyte Li3InCl6, polyvinylidene fluoride, carboxymethyl cellulose, and polydimethylsiloxane were mixed in a mass ratio of 86:5:3:6 to prepare a slurry. The slurry was then roller-coated onto both sides of a polyethylene membrane and dried to obtain a coated diaphragm.
[0105] Cell manufacturing A coated separator with a thickness of 20 μm is placed between the positive electrode and the negative electrode prepared above. Then, the sandwich structure composed of the positive electrode, the negative electrode and the separator is stacked and packaged with aluminum-plastic film to produce a soft-pack battery cell with a capacity of 1Ah ready for liquid injection.
[0106] The battery is obtained by injecting electrolyte and forming the cells.
[0107] Examples 2-6 Examples 2-6 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1 above, except that the formulation in Table 1 is used.
[0108] Table 1 Examples 7-12 Examples 7-12 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1 above, except that the formulation in Table 2 is used.
[0109] Table 2 Examples 13-14 Examples 13-14 illustrate the battery disclosed in this invention, including most of the operating steps in Example 1 above, except that the particle size of the positive electrode active material adopts the formulation in Table 3.
[0110] Table 3 Comparative Examples 1-3 Comparative Examples 1 to 3 are used to illustrate the battery disclosed in this invention, including most of the operating steps in Example 1, except that they use the formulations in Tables 1 to 3.
[0111] Performance testing I. The following performance tests were performed on the batteries obtained in the above embodiments and comparative examples: (1) Electrolyte viscosity test: The viscosity of the electrolyte was measured using a Fungilab viscometer and a circulating water bath system at a test temperature of 25℃.
[0112] (2) Electrolyte ionic conductivity test: The ionic conductivity of the electrolyte system was tested using an ionic conductivity meter, and the temperature was controlled at 25℃.
[0113] (3) Rate performance test: After the battery is placed in a constant temperature test chamber at 25℃±2℃ for 1 hour, it is charged to 4.80V with 1C constant current and constant voltage and cut-off current of 0.05C; it is discharged to 3.0V with 2C and 5C current and recorded discharge time, discharge capacity and discharge plateau voltage; the above steps are repeated 100 times and the capacity retention rate is calculated.
[0114] The test results are shown in Table 4.
[0115] Table 4 The test results of Examples 1-6 and Comparative Example 1 show that this application achieves a low electrolyte viscosity of 4-15 mPa·s through the interaction of additives and solvents, while maintaining an ionic conductivity of 2.8-5.1 mS / cm, ensuring excellent rate performance of the battery even at high voltages. The test results of Examples 1, 7-12, and Comparative Example 2 show that by setting a functional layer on the surface of the negative electrode active material layer, the rate performance and cycle performance of the battery can be further improved. The test results of Examples 1, 13, 14, and Comparative Example 3 show that a higher K90 value results in better rate performance. When K90 is less than 0.6, the rate performance and cycle performance of the battery decrease.
[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A battery, characterized in that, The device includes an electrolyte, a negative electrode, and a positive electrode. The electrolyte comprises a lithium salt, additives, and a solvent. The additives include at least two of the following: fluoroethylene carbonate, 1,3-propane sulpholol, vinylene carbonate, vinyl sulfate, lithium supplement, tris(trimethylsilane) phosphate, tris(trimethylsilyl)borate, dimethyldimethoxysilane, and ionic liquids. The solvent includes at least one of the following: silane solvents and ether solvents. The negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer, and a functional layer. The negative electrode active material is disposed on at least one side of the negative electrode current collector, and the functional layer is disposed on the side of the negative electrode active material layer opposite to the current collector. The functional layer is an SEI layer and / or a lithium alloy layer. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes a positive active material.
2. The battery according to claim 1, characterized in that, The silane solvent includes one or more of trimethylmethoxysilane, methyltrimethoxysilane, tetramethyl orthosilicate, (3,3,3-trifluoropropyl)-dimethylmethoxysilane, and (3,3,3-trifluoropropyl)-trimethoxysilane; And / or, the ether solvent includes one or more of the following: fluoroether compounds, 2-dimethoxyethane, ethylene glycol dimethyl ether, dimethoxydimethyl ether, diethylene glycol dimethyl ether, 1,3-dioxolane, triethylene glycol monoethyl ether, tetrahydrofuran, and 2-methyl-tetrahydrofuran; The fluoroether compounds include one or more of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, methoxynonfluorobutane, ethoxynonfluorobutane, and 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane.
3. The battery according to claim 1, characterized in that, The ionic liquid comprises one or more of the following: 1-methyl-propylpyrrolidone bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpiperidine bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidine bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidine bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidone bis(fluorosulfonyl)imide, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide. And / or, the lithium supplement includes one or more of lithium nitrate, lithium borate, lithium difluorooxalate borate, lithium difluoro(bis(oxalate) phosphate), and lithium difluorophosphate.
4. The battery according to claim 1, characterized in that, The mass of the additive is 0.01% to 10% of the mass of the solvent, and the concentration of the lithium salt is 1 to 4 mol / L.
5. The battery according to claim 1, characterized in that, The SEI layer includes one or more of lithium fluoride, lithium oxide, lithium sulfide, lithium nitride, and lithium phosphide. And / or, the lithium alloy layer comprises an alloy formed of metallic lithium with one or more of gold, indium, magnesium, zinc, chromium, nickel, molybdenum, tungsten, vanadium, titanium, niobium, zirconium, cobalt, manganese, aluminum, copper, boron, silver, tin, silicon, carbon, phosphorus, and bismuth.
6. The battery according to claim 1, characterized in that, The thickness of the functional layer is 0.2~20μm.
7. The battery according to claim 1, characterized in that, The particle size distribution of the positive electrode active material satisfies K90 > 0.
6.
8. The battery according to claim 1, characterized in that, The positive electrode current collector and the negative electrode current collector are each independently selected from metal current collectors and / or composite current collectors; The composite current collector includes a base film, a substrate layer, and a conductive layer. The substrate layer is disposed between the base film and the conductive layer and is located on at least one side of the base film. The substrate layer includes at least one of nickel and titanium.
9. The battery according to claim 8, characterized in that, The negative electrode current collector further includes a coating layer, which is disposed on at least one surface of the metal current collector and located between the negative electrode active material layer and the metal current collector; and / or, the coating layer is disposed between the underlayer and the conductive layer; The coating includes one or more of the following elements: nickel, zinc, tin, silver, magnesium, iron, aluminum, and boron.
10. The battery according to claim 8, characterized in that, When the positive current collector and the negative current collector are selected from composite current collectors, both the positive electrode sheet and the negative electrode sheet are provided with adapter tabs and external tabs. The adapter tabs are welded to the conductive layer. The conductive layer, on the side facing away from the base film, is provided with an adapter tab connection area, a blank area and an active material area for coating active materials in sequence along its length direction. The adapter tab includes a first connection area and a second connection area. The first connection area is connected to the adapter tab connection area and partially connected to the blank area. The end of the second connection area away from the blank area is soldered to the external tab. The length of the first connection area is less than or equal to the length of the blank area, the length of the second connection area is less than or equal to the length of the first connection area, and the width of the first connection area is greater than the width of the second connection area.
11. The battery according to claim 10, characterized in that, The first connection area is welded to the adapter tab connection area. The weld marks are spaced apart and are diamond, square, or circular in shape. The gap between two adjacent weld marks is 0.1-1 mm.
12. The battery according to claim 11, characterized in that, When the solder mark is rhomboid, the ratio of the diagonal lengths of the solder mark is 1:1 to 5:1; And / or, when the solder mark is square, the diagonal length of the solder mark is 1.44~7mm; And / or, when the solder mark is circular, the diameter of the solder mark is 1~5mm.
13. The battery according to claim 10, characterized in that, The cross-sectional area of the external electrode is 0.05-40 mm. 2 ; And / or, the thickness of the outer tab of the positive electrode sheet is 100~300μm, the width is 5~65mm, and the length is 20~60mm; The thickness of the external tab of the negative electrode sheet is 100~400μm, the width is 5~65mm, and the length is 20~60mm.
14. The battery according to claim 1, characterized in that, The battery also includes a separator, which is a polymer porous base membrane or a coated separator. The coated separator includes a polymer porous base membrane and a functional coating disposed on at least one side of the polymer porous base membrane. The polymer porous base membrane includes at least one of polyethylene and polypropylene; the functional coating includes one or more of ion conduction enhancers, polymer binders, thickeners, and wetting agents.
15. The battery according to claim 14, characterized in that, The ion conduction enhancer includes one or more of the following: oxide solid electrolyte, halide solid electrolyte, sulfide solid electrolyte, alumina, boehmite, zinc oxide, zirconium dioxide, titanium dioxide, barium sulfate, polyvinylidene fluoride and its copolymers, aramid, polymethyl methacrylate and its modifiers.
16. An electrical appliance, characterized in that, Includes the battery as described in any one of claims 1 to 15.